The influence of the psychological state on the physical fitness of cadets of educational organizations of the ministry of internal affairs of Russia - S. V. Kasyanov; A. I. Zemlyanoy; A. A. Tashiyan (Вестник Северо-Кавказского федерального университета, 2023)
The article examines the consequences of the negative impact of mental health on physical fitness, as well as the key conditions under which a balance is achieved between the specified conditions of the functioning of the body in full. The purpose of the article is to consider the influence of the moral and psychological state of students of educational organizations of the Ministry of Internal Affairs of Russia on their physical well-being. To achieve this goal, the methods of structural, systemic and functional analysis, the method of comparative research, psychological methods, methods of hypothesis building, theoretical modeling, as well as methods of specific sociological research were used. In the introduction to the article, mental and physical health are considered – two components that determine the normal state of the body. These elements are complementary and defining each other. When conducting scientific research, the authors used general scientific methods of cognition of objective reality. The results obtained in the process of psychological and pedagogical research can serve as a theoretical basis for the physical training of cadets of educational organizations of the Ministry of Internal Affairs of Russia.